Poetry poetess in professional music (Czech Journal of Multidisciplinary Innovations, 2023)
This article presents judgments about the beautiful expression of the literary heritage of women poets who actively worked in different periods of the history of Uzbek literature and are perfectly applied in samples of Uzbek professional music. In particular, we are talking about "Mustakhzod" performed by the gazelles of Mokhlaroim-Nadir, "Chorgokh 1", "Chorgokh 2" performed by the gazelles Jahan atin-Uvaysiy and "Samarkand Ushshoggi" performed by the gazelles of Zebunnis.